Relating Requirements to Implementation via Topic Analysis - Hindle, Abram; Bird, Christian; Zimmermann, Tom; Nagappan, Nachi (Proceedings of the 2012 International Conference on Software Maintenance (ICSM 2012), 2012)
Large organizations like Microsoft tend to rely on formal requirements documentation in order to specify and design the software products that they develop. These documents are meant to be tightly coupled with the actual implementation of the features they describe. In this paper we evaluate the value of high-level topic-based requirements traceability in the version control system, using Latent Dirichlet Allocation (LDA). We evaluate LDA topics on practitioners and check if the information extracted matches the perception that Program Managers and Developers have about the effort put into addressing certain topics. We found that effort extracted from version control that was relevant to a topic often matched the perception of the managers and developers of what occurred at the time. Furthermore we found evidence that many of the identified topics made sense to practitioners and matched their perception of what occurred. But for some topics, we found that practitioners had difficulty interpreting and labelling them. In summary, we investigate the high-level traceability of requirements topics to version control commits via topic analysis and validate with the actual stakeholders the relevance of these topics extracted from requirements.